Host selection of the tobacco whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) among four pepper cultivars (Capsicum spp.), Thailand - ศรีพลแท่น, ยุวธิดา; Chiu, Chun-I; Charoensak, Khakhanangk; Sukthongsa, Natthawut (วารสารแก่นเกษตร, 2021)
The tobacco whitefly Bemisia tabaci (Gennadius) causes yield loss of a variety of plants by infesting and transferring viruses. Host-plant resistance to B. tabaci could potentially reduce its impact. However, resistance is low in most Thai pepper (Capsicum spp.) cultivars. In this study, we evaluated host-plant resistance of four common pepper cultivars in Thailand, including C. annuum cv. Jinda, C. annuum cv. Yuak, C. frutescens cv. Keenu (= Khinu), and C. chinensis cv. Karang (= Kareang or Kariang), by quantifying plant attraction, egg-laying preference, feeding activity, and growth performance of B. tabaci in relation to the four cultivars. Our results showed that C. annuum cv. Jinda and C. annuum cv. Yuak are less attractive to B. tabaci adults, which had a significantly lower egg-laying preference and less feeding activity in relation to C. annuum cv. Jinda. No difference in total growth duration of B. tabaci was found in regards to the different cultivars. We believe that C. annuum cv. Jinda has traits that deter or repel the B. tabaci adults and inhibit their feeding activities.